Optimalisasi Kader Kesehatan melalui Senam Low Back Pain di Era Pandemi bagi Masyarakat Desa Jetis Kabupaten Sukoharjo: Optimizing Health Cadres through Low Back Pain Gymnastics in the Pandemic Era for the Community of Jetis Village, Sukoharjo Regency - Maryatun Maryatun; Ari Sapti Mei Leni; Indarwati Indarwati; Ipa Sari Kardi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
In the pandemic era, public anxiety about illness continues to increase. A person who experiences pain in the spine will feel worried about what he feels. Posyandu is community empowerment that helps improve the health status of the community in their environment. Health Posyandu will usually have cadres who assist in the implementation of service activities. Good health cadres will be able to manage Posyandu by mobilizing the surrounding community to live healthily in order to create optimization in the health sector. However, many health cadres in their services are less able to provide services for posyandu activities. Following are the results of distributing questionnaires on low back pain gymnastics, it was stated that 87 health cadres could not do exercise because they had never received training. Knowledge and low back pain gymnastics skills from the results of the study can reduce the pain felt by a person, therefore community service is carried out to minimize back pain in the elderly. Community service consists of four stages. The first stage is situation analysis, planning, implementation, and evaluation monitoring. The population in this study was 17 elderly posyandu cadres. Sampling using total sampling. The results of the evaluation of LBP counseling were 15% pre-extension knowledge and 68% post-extension knowledge. The results of the evaluation of pre-training skills prevention and handling skills were 13% and post-training skills were 65%. The conclusion is that there is an increase in the knowledge and skills of the LBP prevention and handling of elderly posyandu cadres.